"Personal Opinion" in Qurʾānic Exegesis: Medieval Debates and Interpretations of al-Tafsīr bi-l-Raʾy - Kulinich, Alena 19XX- (Der Islam, 2022)
This article explores the long-contested question about the role of individual judgement vis-à-vis the authority of tradition in the interpretation of the Qurʾān. It focuses on the notion of al-tafsīr bi-l-raʾy - interpretation of the Qurʾān by "personal opinion" - and offers an insight into medieval Muslim debates over the legitimacy of this type of exegesis, its alleged prophetic disapproval, and the scope and conditions of its use. Based on the Sunnī tafsīr works from the 3rd/9th to the 6th/12th centuries, the article examines how in the course of these debates Muslim authors negotiated the meaning of al-tafsīr bi-l-raʾy . Against the view that it encompassed any interpretation beyond tradition-based tafsīr , their reinterpretations of the term implied that philological, juridical, and Ṣūfī tafsīr could not be categorized as al-tafsīr bi-l-raʾy , thereby narrowing the meaning of this concept and broadening the scope of legitimate exegesis and interpretative authorities in Sunnī tafsīr tradition.